Istihalah as an alternative method in halal industry with special reference to ceramic products from animal bone - Deuraseh, Nurdeng @ Nurdeen; Mohd Salleh, Mohd Mahyeddin; Jamaludin, Mohammad Aizat (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
The ceramic product derived from non-halal animal bone has become an issue of Muslims whether it is halal or haram for usage. The status can be determined by scrutinizing at istihalah process either a complete change (istihalah kamilah) or incomplete change (istihalah ghayr kamilah). This research applies qualitative research method via document analysis approach to examine the various opinions of the classical and current Islamic jurists. The research discovers an alternative method in processing ceramic product from animal bone through istihalah. It is a transformation of filthy or haram materials into other materials which includes physical appearance and its properties such as odor, taste and color.